THE DESCRIPTION OF AVAILABILITY OF CLEAN WATER IN JORONG PALUPUAH PASIA LAWEH, WEST SUMATRA - DESSY ANGRAINI; Iza Ayu Saufani (STIKes Hang Tuah Pekanbaru, 2020)
Era SDGs (sustainable development goals) is a continuation MDGs (MillenniumDevelopment Goals) have a common goal that is universal to maintain the balance of the three dimensions of sustainable development, one of its objectives is to ensure the availability of clean water and sustainable sanitation for everyone. The importance of the availability of clean water for people's lives can have an important influence on public health, so that the water used for daily needs must meet quality standards for environmental health quality and water health requirements. Based on information from Wali Nagari Palupuah, said that the source of water used by residents for their daily needs is physically colored, there are deposits in water reservoirs, and have never been tested for safety. This study aims to determine the description of the availability of clean water in Jorong Palupuah Nagari Pasia Laweh, Agam. This research is an observational survey research with research design cross sectional. The population in this study were all households in Jorong Palupuah Nagari Pasia Laweh Agam, West Sumatra. The sample of 74 KK was determined by proportionate stratified random sampling technique and data analysis was carried out by univariate. The results showed that the characteristics of respondents in jorong Palupuah Nagari Pasia Laweh Agam, West Sumatra the majority aged 25-45 years with the last level of education was graduated from high school. Based on the survey results, the average number of family members in Jorong Palupuah numbered 3 people (32.4%), and the majority of respondents worked as IRT with an average family income level of Rp. 1,500,000. There are five main sources of raw water that are used as a source of clean water by the jorong community and most of the water sources used come from springs (71.8%). In addition, there are still some people who complain that water supply is not smooth (35.1%). And there are still 41.9% who say it is not easy to get clean water. The quality of clean water supplied in Jorong Palupuah is included in the good category. However, most people do not use PDAM and the water sources used are not very supportive for consumption